FINANCIAL PERFROMANCE MEASUREMENT OF THE ONE PET SHOP MAKASSAR - Ferdinandus Sampe; Beauty (AJAR, 2026)
The purpose of this study was to determine the measurement of financial performance at the One Pet Shop Makassar. The study was conducted by collecting data for the last three year, from 2023 to 2025. The researchers compared the results with the ideal standards that have been set and given a score according to the criteria. Data analysis was carried out with financial analysis. The analysis results of financial performance of the The One Pet Shop Makassar reveal those ROI, TATO and profit margin on sales decreased while ROE and profit margin increased. Based on the ratio analysis, the financial performance of the firm can be categorized as less  favorable. It is suggested that firm management to improve profitability and total asset turnover.